Dietary fibre in Europe: current state of knowledge on definitions, sources, recommendations, intakes and relationships to health. Issue 2 (5th July 2017) - Stephen, Alison M.; Champ, Martine M.-J.; Cloran, Susan J.; Fleith, Mathilde; van Lieshout, Lilou; Mejborn, Heddie; Burley, Victoria J.
Abstract: Research into the analysis, physical properties and health effects of dietary fibre has continued steadily over the last 40–50 years. From the knowledge gained, countries have developed guidelines for their populations on the optimal amount of fibre to be consumed each day. Food composition tables from many countries now contain values for the dietary fibre content of foods, and, from these, combined with dietary surveys, population intakes have been determined. The present review assessed the uniformity of the analytical methods used, health claims permitted, recommendations and intakes, particularly from national surveys across Europe and around the world. It also assessed current knowledge on health effects of dietary fibre and related the impact of different fibre types on health. The overall intent was to be able to provide more detailed guidance on the types of fibre which should be consumed for good health, rather than simply a total intake figure, the current situation. Analysis of data indicated a fair degree of uniformity in the definition of dietary fibre, the method used for analysis, the recommended amount to be consumed and a growing literature on effects on digestive health and disease risk. However, national dietary survey data showed that intakes do not reach recommendations and very few countries provide guidance on the types of fibre that are preferable to achieve recommended intakes. Research gaps were identified and ideas suggested to provide information for more detailed advice to the public about specific food sources that should be consumed to achieve health benefits.